THE DIALECTICS OF JAVANESE AND ISLAMIC CULTURES: AN INTRODUCTION TO KUNTOWIJOYO'S THOUGHT - ZTF, Pradana Boy (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2015)
AbstractThe main idea of this paper is to show the attempts made by Kuntowijoyo, anIndonesian unrivalled great thinker, to synthesize Javanese and Islamic worldviews through his writings. KuntowijoyoÄ±s thought is much influenced by his social circumstances. This manifested in the values, philosophies, and worldviews he was attempting to synthesize. One of KuntowijoyoÄ±s concerns is demystification. In this context, it is not surprising that the presentation of mythical practices in Javanese society is somehow dominant. The presentation is not intended as an agreement, but rather as evidences on the irrationality of the myths.Another aspect that should be underlined is Sufism and transcendence. In this aspect, the synthesis of Javanese and Islamic elements are a bit more visible as represented in his novel Khutbah di Atas Bukit that is seen as that is seen as resemblance of Kisah Dewa Ruci in Javanese literature by many observers.Key words: Dialectics, Javanese Thought.